Cross Section Study of Malnutrition in Children of 1-10 Years Age Group in Urban Slums of Aligarh (Global Journal of Medical Research, 2013)
Nutrition plays important role in development of growth and development of child. In many developing countries poor nutritional status is mainly due to illiteracy, poverty, least job opportunities etc. Poor hygiene, intestinal infection, worm infestation are another important groups leading malnutrition in India. Cross sectional study was conducted in Bhojpuri slum which is densely Muslim populated slum of Aligarh City, Uttar Paradesh on 300 children. Objective of the study was to assess the nutritional status of children below ten years of age. Measurement of height and weight was done by weighing machine and measuring scale removing shoes with minimal clothing. To measure the stunting of children enrolled in this study, height of the children measured during study was compared with expected height for age. The magnitude of stunting was decided on the basis of Water low classification and was stastically analyzed using chi square test. Our study also revealed that incidence of grade III malnutrition in 7-10 year age group was highest (27.7%). Present study also concluded that prevalence of stunting among the children of Bhujpura Slum was more prevalent than wasting. It was found that out of 300 children 248 (83%) were stunted and male female proportion was 162 (65%) and 86 (34.7%) respectively. Malnutrition prevalent in these children can be attributed to their low socio economic status, poverty and early age of employment.
Keywords: malnutrition; stunning; children